Acute myeloid leukemia: a retrospective claims analysis of resource utilization and expenditures for newly diagnosed patients from first-line induction to remission and relapse. (4th March 2017) - Irish, William; Ryan, Michael; Gache, Larry; Gunnarsson, Candace; Bell, Timothy; Shapiro, Mark
Abstract: Objective: The objective of this study was to estimate resource utilization and expenditures for patients with acute myeloid leukemia (AML) in a real-world claims database. Research design and methods: AML patients were identified in MarketScan claims databases between 1 January 2009 and 31 January 2015. Patients had a minimum of two AML diagnosis codes, hospitalization within 14 days after initial diagnosis, and ≥6 months of enrollment before initial diagnosis. Patients were monitored from first-line induction to a record of remission. A subset had a record of a second treatment period, defined as time from relapse to remission. Patient demographics, AML risk factors, and comorbidities were recorded. Descriptive analysis of utilization and expenditures (in 2014 US) were reported for each cohort. Results: The inclusion criteria were met in 1597 patients (mean age, 58.4 years; 51.0% male). Ninety percent of patients had ≥1 risk factor for AML. Mean (SD) healthcare expenditures for patients from first-line induction to remission ( n = 681) were 208, 857 (152, 090). Of the 157 who had a record of relapse, 70 had a record of a second remission. Expenditures for these patients ( n = 70) from relapse to remission were 142, 569 (208, 307); 60% were admitted to a hospital for a mean of 18.5 hospital days, and 20% had ≥1 emergency room visit. Conclusions: Although this claims-based analysis is limited by a lack of generalizability to noninsured populations and potential underreporting of certain events and diagnoses, we found that treating AML patients poses a significant healthcare burden, during both first-line induction and relapse. With people living longer, the number of cases of AML is expected to increase in the future.